SYNERGY OF TRADITIONAL AND MODERN APPROACHES TO THE SEARCH AND STUDY OF PROMISING NATURAL-ORIGIN DRUG CANDIDATES (HISTORY, CHALLENGES, SOLUTIONS) - Vladimir Gennadievich Luzhanin; Natalia Eduardovna Kolomiets; Yaroslav Evgenievich Reshetov; Andrey Kenneth Waillie; Anastasia Olegovna Weilly; Roman Sergeevich Boev; Mikhail Valerievich Belousov (Химия растительного сырья, 2025)
Until the beginning of the 21st century researchers spent decades searching for new natural sources of medicines using so-called 'traditional classical' chemical, physical-chemical, in vitro and in vivo methods. The use of this method has allowed the discovery of numerous plants that have become a source of valuable medicinal preparations. However, all of them require significant financial and time investments. Therefore, scientists faced the challenge of rationalizing the process of searching for promising candidates, reducing the time and financial costs of preclinical and clinical research phases, and increasing the efficiency of the final outcome.Increasingly popular modern method of searching for prospective plant-origin drug candidates is in silico, using on-line services and platforms, each of which individually has disadvantages. The most effective is the integration of several service databases.This allow researchers to identify possible directions for studying the combined effects of isolated substances, thereby reducing the volume of necessary experimental studies in vitro and in vivo.The combination of traditional methods of isolation and structure determination with modern in silico methods for determining biological activity is confirmed by literature data and our research, in which the combination identified species that are promising for further study.